Konsumsi dan Kecernaan Zat Makanan Pada Kambing Peranakan Etawah Jantan Yang Diberi Ransum Komplit Berbasis Jerami Padi Terfermentasi - Cut Intan Novita (Jurnal Agripet, 2007)
ABSTRACT. Fermentation of rice straw incriased its nutritive value, digestibility and palatability. The aim of the present experiment was to study the effect of feeding rations composed of fermented rice straw supplement with urea and probiotic, and mixed with concentrate. Eighteen Etawah -grade bucks (age 1.5 years) were assigned into a completely randomized design to study nutrient intake and apparent degestibility of three dietary treatments. The rations as treatments were as follow: CFR=concentrate + chopped fermented rice straw:; Complete=concentrate + groud fermented rice straw; ELG = concentrate + elephan grass. Dry matter (DM) and crude protein (CP) intake of bucks were not different significantly among treatments. Apparent degestibility of DM was not different, however CP was significantly lower (p0.05) for the GFR treatments compared to the other two treatments. These results suggest that fermented rice straw can be uded to substituse the fresh elephant grass.